Duodenal mucosal resurfacing: Multicenter experience implementing a minimally invasive endoscopic procedure for treatment of type 2 diabetes mellitus - van Baar, Annieke C.G.; Haidry, Rehan; Rodriguez Grunert, Leonardo; Galvao, Manoel P. Neto; Bisschops, Raf; Hayee, Bu Hussain; Costamagna, Guido; Deviere, Jacques; Bergman, Jacques J.G.H.M. (Endoscopy International Open, 2020)
Background and study aims Duodenal mucosal resurfacing (DMR) is an endoscopic procedure which improves insulin resistant metabolic disease, including type 2 diabetes mellitus (T2DM). The aim of this report was to evaluate the feasibility and procedural aspects of DMR and to provide more specific DMR procedural guidance for endoscopists.Patients and methods In this international multicenter, prospective, open-label study, patients on oral anti-diabetic agents for treating T2DM underwent single DMR. DMR entails circumferential submucosal lifting followed by circumferential mucosal hydrothermal ablation using an over-the-guidewire balloon catheter for lifting and ablation. For the first 28 patients a dual catheter system was used. During the study, a new integrated catheter was developed which was used for the latter 18 patients. During DMR, procedure success (complete DMR: duodenal ablation length ≥ 9 cm) and procedure duration were captured.Results Forty-six patients underwent DMR. Using the dual catheter system, a complete DMR was performed in 22 of 28 patients (79 %). In the next eighteen patients who underwent DMR with the integrated catheter, a complete DMR was performed in 15 of 18 patients (83 %). The integrated catheter facilitated the DMR procedure and resulted in a reduction in procedure time. A detailed table and video are provided for future endoscopists.Conclusions In our multicenter study, DMR was found to be feasible in the hands of experienced endoscopists. The integrated DMR catheter was a welcome modification during the study, allowing for easier ablation administration. Further optimization of the technique would be valuable prior to widespread dissemination.